'People's English' in South Africa : theory and practice - Butler, Ian (Rhodes University, Faculty of Education, Department of Education, 1994)
Communicative Language Teaching, an approach to language teaching currently widely prescribed, has been criticised for its unquestioning acceptance of the cultural and political norms of the target language. People's English (an aspect of the larger People's Education movement), on the other hand, offers a philosophy and methodology that takes an actively critical view of language and its relationship to power. In the context of South African society, this stance has had clear political implications. Although still imprecisely defined , the concepts of People's Education and People's English have been debated and discussed by various ant-apartheid movements in recent years. Attempts have also been made to translate the evolving theory into practice through the development of materials and methodologies. This has been achieved on a relatively small scale, with varying degrees of success. Recent reform measures by the South African government have, however, prompted the proponents of People's Education to reassess their position. This thesis presents a historical overview and critical assessment of the development of People's English in South Africa.
Keywords: English language -- Study and teaching -- South Africa; Second language acquisition -- South Africa